(S)-Thienyl and (R)-Pirydyl phosphonate Derivatives Synthesized by Stereoselective Resolution of Their Racemic Mixtures With Rhodotorula mucilaginosa (DSM 70403) - Scaling Approaches - Lubiak-Kozłowska, Katarzyna; Brzezińska-Rodak, Małgorzata; Klimek-Ochab, Magdalena; Olszewski, Tomasz K.; Serafin-Lewańczuk, Monika; Żymańczyk-Duda, Ewa (Frontiers in Chemistry, 2020)
Rhodotorula mucilaginosa was successfully applied as a biocatalyst for the enantioselective resolution of the racemic mixtures of heteroatom phosphonates derivatives, resulting in receiving the following enantiomers: (S)-1-amino-1(2-thienyl)methylphosphonic acid (Product 1) and (R)-1-amino-1-(3′pirydyl) methylphosphonic acid (Product 2). Biological synthesis of both products is reported for the first time. Pure (S)-1-amino-1-(2-thienyl)methylphosphonic acid (Product 1) was isolated with a conversion degree of 50% after 24 h of biotransformation was conducted on a laboratory scale under moderate conditions (1.55 mM of substrate 1, 100 mL of distilled water, 135 rpm, 25°C; Method A). The scale was enlarged to semi-preparative one, using a simplified flow-reactor (Method C; 3.10 mM of substrate 1) and immobilized biocatalyst. The product was isolated with a conversion degree of 50% just after 4 h of biotransformation. Amino-1-(3′pirydyl)methylphosphonic acid (Substrate 2) was converted according to novel procedure, by the immobilized biocatalyst - Rhodotorula mucilaginosa. The process was carried out under moderate conditions (3.19 mM – substrate 2 solution; Method C1) with the application of a simplified flow reactor system, packed with the yeasts biomass entrapped in 4% agar-agar solution. Pure (R)-amino-1-(3′pirydyl)methylphosphonic (50% of conversion degree) was received within only 48 h.